Surface chemistry engineering and the applications of MXenes - Guohao Li; Shuhan Lian; Jie Wang; Guanshun Xie; Nan Zhang; Xiuqiang Xie (Journal of Materiomics, 2023)
MXenes have captured extensive attention in various fields by virtue of unique hydrophilicity, high conductivity and tunable surface terminations. In this review, the state-of-the-art progresses of designing functional MXenes have been summarized. Firstly, the synthesis methods of MXenes are summarized and classified into HF etching, in-situ HF etching and fluoride-free etching approaches based on the effect on the surface chemistry of MXenes. Secondly, the factors that affect the surface termination groups are discussed, including synthesis methods, heat treatment temperature and atmosphere. Thirdly, this review gives an overview of the synthetic routes of functional MXenes including termination modification by synthesis methods and heat treatment, heteroatom (N, S, or P) doping, cation and organic molecule intercalation and hybridization with polymer, which inhibit restacking and increase active sites for intrinsically enhancing the inherent physical and chemical properties of MXenes. Finally, the applications with respect to energy storage and conversion, catalysis, sensors, electromagnetic interference shielding and microwave absorption of functional MXenes are introduced. Additionally, the critical challenges and development prospects of functional MXenes are also highlighted.